EFFECT OF BUILDUP FACTORS ON INDOOR GAMMA DOSE RATE. Issue 2 (6th July 2020) - Manić, V; Manić, G; Nikezić, D; Krstić, D
Abstract: The effect of buildup factors on absorbed dose rate in air and the effective dose from gamma rays of primordial radionuclides in building materials, was investigated in the article. Specific absorbed dose rates were calculated for the standard concrete room, as well as, for rooms where brick and covering building materials were used. For all room models the Harima (G-P) buildup factors were applied, while for the standard room the Berger's and Taylor's buildup factors were used, too. The contribution of the radiation buildup to absorbed dose rate and effective dose was determined as large as 41%.